Improving Prognosis of Surrogate Assay for Breast Cancer Patients by Absolute Quantitation of Ki67 Protein Levels Using Quantitative Dot Blot (QDB) Method - Hao, Junmei; Lyu, Yan; Zou, Jiarui; Zhang, Yunyun; Xie, Shuishan; Jing, Lili; Tang, Fangrong; Lyu, Jiahong; Zhang, Wenfeng; Zhang, Jianbo; Wang, Xunting; Chen, Kuisheng; et al. (Frontiers in Oncology, 2021)
Background: Immunohistochemistry (IHC) based-surrogate assay is the prevailing method in daily clinical practice to determine the necessity of cytotoxic therapy for Luminal-like breast cancer patients worldwide. It relies on Ki67 scores to separates Luminal A-like from Luminal B-like breast cancer subtypes. Yet, IHC-based Ki67 assessment is known to be plagued with subjectivity and inconsistency to undermine the performance of surrogate assay. Novel method needs to be explored to improve the clinical utility of Ki67 in daily clinical practice. Materials and methods: The Ki67 protein levels in a cohort of 253 specimens were assessed with IHC and Quantitative Dot Blot (QDB) methods respectively, and used to assign these specimens into Luminal A-like and Luminal B-like subtypes accordingly. Their performances were compared with the Kaplan-Meier, univariate and multivariate survival analyses of the overall survival (OS) of Luminal-like patients. Results: The surrogate assay based on absolutely quantitated Ki67 levels (cutoff at 2.31 nmole/g) subtyped the Luminal-like patients more effectively than those based on Ki67 scores (cutoff at 14%) (Log rank test, p=0.00052 vs p=0.031). It is also correlated better with OS in multivariate survival analysis [Hazard Ratio (HR) at 6.89 (95%CI: 2.66-17.84, p=0.0001) vs 2.14 (95%CI: 0.89-5.11, p=0.087)]. Conclusions: Our study showed the performance of surrogate assay may be improved significantly by measuring Ki67 levels absolutely, quantitatively and objectively using QDB method.